Konsep Kedisiplinan Belajar Dalam Kitab Kifayatul Atqiya Bab Hifdzul Auqot Karya Abubakar Bin Markhum Muhammad Syato’ - Soliyah Soliyah; Muchotob Hamzah; Ali Mu’tafi (Institut Nalanda, 2024)
Learning discipline is seen as a factor influencing students' learning outcomes. Attitudes and behaviors of discipline do not form spontaneously or quickly, but through a rather lengthy process. The aim of this research is to provide a detailed explanation of the concept of learning discipline found in the book Kifayatul Atqiya, specifically in the chapter Hifdzul Auqot. This includes definitions, scope, and emphasized aspects within the context of learning discipline as per the perspective presented by Abubakar bin Markhum Muhammad Syato’. The type of research used in this thesis is a literature review (library research). The research approach employed is Qualitative Research, which aims to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals or groups.